Bone mineral density and trabecular bone score, hyperuricemia and metabolic syndrome in postmenopausal women - G.S. Dubetska (Bolʹ, Sustavy, Pozvonočnik, 2020)
The article presents the results of independent study of hyperuricemia peculiarities among the women in postmenopausal period, taking into account indicators of body mass index, lipid metabolism and bone mineral density. The higher level of uric acid was found among women in postmenopausal period with maximal body mass index (BMI > 35), with the highest degree of obesity. Significant correlation was determined between uric acid and triglyceride (r = 0.26, p < 0.05), atherogenic coefficient (r = 0.24, p < 0.05) among women in postmenopausal period. The incidence of osteoporosis in women with hyperuricemia was lower than the one of women who had a normal rate of uric acid: 19 % and 34 % at the level of lumbar spine, and 17 % and 21 % at the level of femoral neck.